Influence of Pamoic Acid as a Complexing Agent in the Thermal Preparation of NiO Nanoparticles: Application to Electrochemical Water Oxidation. Issue 2 (9th January 2018) - Qasem, Mohammed Ameen Ahmed; Aziz, Md. Abdul; Qamaruddin, Muhammad; Kim, Jong‐Pil; Onaizi, Sagheer A.
Abstract: We developed a thermal decomposition method for preparing NiO nanoparticles (NiONPs) using disodium salt of pamoic acid (Na2 PA) as a complexing agent and Ni(NO3 )2 ⋅6H2 O as a nickel precursor. Prior to thermal decomposition, Ni(NO3 )2 ⋅6H2 O was mixed with Na2 PA in ethanol, and the ethanol was evaporated succesively. The dried reaction mass was characterized using Fourier transform infrared spectroscopy, X‐ray photoelectron spectroscopy, and thermal gravimetric analysis. Thermal decomposition was then performed in air to obtain the NiONPs. The role of Na2 PA in the synthesis of NiONP was evaluated by preparing NiONPs according to the protocol described above without the addition of Na2 PA. The X‐ray diffraction data indicated that crystalline NiO (bunsenite, cubic crystal system) formed with or without Na2 PA; however, field emission scanning electron microscopy images showed that smaller monodisperse NiONPs formed only with the addition of Na2 PA. Without Na2 PA, the obtained NPs were quite large and polydisperse. The sizes of the NiONPs prepared in the presence of Na2 PA were determined using transmission electron microscopy imaging to be 19.1 ± 3.2 nm. The electrocatalytic activity of the NiONPs toward water oxidation under alkaline conditions was evaluated by immobilizing the NPs onto an in‐house prepared filter paper derived carbon electrode, and compared. Abstract : A thermal decomposition method for preparing NiO nanoparticles using disodium salt of pamoic acid as a complexing agent and Ni(NO3 )2 ⋅6H2 O as a nickel precursor were developed. The prepared NiO nanoparticles have been used as anode materials toward water electrooxidation in an alkaline medium upon immobilization on in‐house prepared filter paper derived carbon electrode.